Mechanisms of anti-microbial action of tunicate (Polycarpa papillata) extract against methicillin resistant Staphylococcus aureus and methicillin susceptible Staphylococcus aureu - Mohd Yaakob, Haslinda Ayu (2013)
The spread of multi drug-resistant (MDR) organism particularly Methicillin Resistance Staphylococcus aureus (MRSA) has become a public health concern worldwide. The failure to respond to antibiotic therapy has been a great challenge to clinicians in treatment of infection caused by this pathogen. This phenomenon stimulated the escalation to discovery of new antibacterial compounds from various natural resources worldwide including marine organism. A series of researches revealed that marine organism possess biologically active metabolites that signify roles such as antimicrobial, antioxidant, antifungal and antiviral. The objectives of the study are to elucidate the efficacy of tunicate extracts, as antimicrobial agent against MRSA and Methicillin Sensitive Staphylococcus aureus (MSSA) as well as to determine the mode of inhibition. Two different extraction methods were employed at the beginning of this study involving solvent extractions and supercritical fluid extractions (SFE). For solvent extractions, methanol and hexane were used whereas for SFE, the extractions were optimized for pressure, carbon dioxide (CO2) flow rate and the used of co-solvent. Higher yield was obtained by solvent extraction than SFE extraction. As for SFE extraction, the optimum extraction conditions were obtained at 400 bar, 28 g/min CO2 with 3 ml/min cosolvent (methanol) introduced intermittently giving high yield. The antimicrobial activity of all extracts against MRSA and non-MRSA isolates showed that SFE extracts have greater antimicrobial activity against both pathogenic bacterial strains tested when compared to solvent extract. Among all SFE isolates, SFE-F extract is the most potent followed by SFE-C, SFE-B and SFE-A. However SFE-D and SFE-E extract which extracted with methanol continuously only inhibit the growth of MSSA. The composition of the most and the least potent SFE extracts in comparison to solvent extracts, identified through gas chromatography mass spectrometry revealed that the chemical composition of both SFE-D and SFE-F tested were almost similar to hexane extract. However there were additional compounds present in SFE D and SFE-F extract such as 2-decenal, 9-hexadecenoic acid, octadecanoic acid methyl ester and hexadecanoic acid ethyl ester. A number of these compounds were D and SFE-F extract such as 2-decenal, 9-hexadecenoic acid, octadecanoic acid methyl ester and hexadecanoic acid ethyl ester. A number of these compounds were also present in methanol extract. Apart from that the presence of fatty acids, fatty acid esters and aldehydes which were higher in the SFE-F extract may contribute to the antimicrobial activity shown by the extract. Bioassay study of SFE-F and methanol extracts revealed that both Polycarpa papillata extracts showed positive effect in inhibiting the growth of all MRSA and MSSA isolates tested. The time kill assay showed bactericidal activity against both MRSA and MSSA at MIC and 2 times MIC. Cytotoxic effects of SFE-F and methanol extracts were shown to inhibit the growth of vero cells at IC50 2.693 mg/ml and 6.509 mg/ml respectively. The mechanism of action of tunicate extracts was investigated through cellular based approach involving leakage assay. This assay showed evidence of membrane impairment through detection of cytoplasmic material measured at A260 upon treatment with tunicate extracts. Bacterial membrane permeabilizing ability was also utilized in this study whereby the penetration of fluorescence dye into the impaired membrane was investigated through fluorescence microscopy with the aid of SYTO 9 and propidium iodide fluorescence stains. Higher dye penetration rate observed in treated cells than the untreated cells. With this principle, effect of tunicate extracts on membrane synthesis targeting fatty acid synthesis II (FASII) pathway were investigated via molecular biotechnological approaches. The gene expression study of enoyl-acyl carrier protein reductase (fabI) gene was determined by real time polymerase chain reaction. The treatment on both MRSA and MSSA resulted in down-regulation of fabI expression thus induced a conditional lethal phenotype in comparison to untreated sample. In summary, the present study showed that Polycarpa papillata methanol and SFE-F extracts possessed significant in vitro antibacterial activity and the effectiveness of both extracts in affecting membrane synthesis are significantly noted. These findings indicate the promising applications of local marine organism as an alternative antimicrobial agent against MRSA.also present in methanol extract. Apart from that the presence of fatty acids, fatty acid esters and aldehydes which were higher in the SFE-F extract may contribute to the antimicrobial activity shown by the extract. Bioassay study of SFE-F and methanol extracts revealed that both Polycarpa papillata extracts showed positive effect in inhibiting the growth of all MRSA and MSSA isolates tested. The time kill assay showed bactericidal activity against both MRSA and MSSA at MIC and 2 times MIC. Cytotoxic effects of SFE-F and methanol extracts were shown to inhibit the growth of vero cells at IC50 2.693 mg/ml and 6.509 mg/ml respectively. Themec hanism of action of tunicate extracts was investigated through cellular based approach involving leakage assay. This assay showed evidence of membrane impairment through detection of cytoplasmic material measured at A260 upon treatment with tunicate extracts. Bacterial membrane permeabilizing ability was also utilized in this study whereby the penetration of fluorescence dye into the impaired membrane was investigated through fluorescence microscopy with the aid of SYTO 9 and propidium iodide fluorescence stains. Higher dye penetration rate observed in treated cells than the untreated cells. With this principle, effect of tunicate extracts on membrane synthesis targeting fatty acid synthesis II (FASII) pathway were investigated via molecular biotechnological approaches. The gene expression study of enoyl-acyl carrier protein reductase (fabI) gene was determined by real time polymerase chain reaction. The treatment on both MRSA and MSSA resulted in down-regulation of fabI expression thus induced a conditional lethal phenotype in comparison to untreated sample. In summary, the present study showed that Polycarpa papillata methanol and SFE-F extracts possessed significant in vitro antibacterial activity and the effectiveness of both extracts in affecting membrane synthesis are significantly noted. These findings indicate the promising applications of local marine organism as an alternative antimicrobial agent against MRSA.